New records and data on rust fungi (Pucciniales, Basidiomycota) in Benin - Tabe, Affoussatou; Aime, M. Catherine; Soulemane Yorou, Nourou; Piepenbring, Meike (Phytotaxa, 2022)
The documentation of rust fungi in tropical Africa is very incomplete. For West Africa, 332 species of rust fungi (Pucciniales, Basidiomycota) are recorded, including only six species from Benin. By a recent survey of rust fungi in Benin, 22 specimens representing 11 species of Pucciniales were found. These species were identified based on morphological characteristics observed by light microscopy. Nine species represent new records of rust fungi for Benin. Among them, Neophysopella tropicalis on Vitis sp. is recorded for Africa for the first time. Nucleotide sequences of the LSU region of ribosomal DNA confirmed identifications of five species, for which sequences were available in GenBank for comparison. For three species, annotated LSU and ITS barcode sequences are provided for the first time. Puccinia canaliculata var. tenuis on Cyperus spp., described from South Africa and recorded for Guinea as well as for Benin, is treated as Puccinia doidgeae nom. nov., based on morphological and sequence data.